Death and the body in the eighteenth-century novel - Zigarovich, Jolene, 1970- (Philadelphia, Pennsylvania : University of Pennsylvania Press, 2023)
Death and the Body in the Eighteenth-Century Novel demonstrates that archives continually speak to the period's rising funeral and mourning culture, as well as the increasing commodification of death and mourning typically associated with nineteenth-century practices. Drawing on a variety of historical discourses--such as wills, undertaking histories, medical treatises and textbooks, anatomical studies, philosophical treatises, and religious tracts and sermons--the book contributes to a fuller understanding of the history of death in the Enlightenment and its narrative transformation.Death and the Body in the Eighteenth-Century Novel not only offers new insights about the effect of a growing secularization and commodification of death on the culture and its productions, but also fills critical gaps in the history of death, using narrative as a distinct literary marker. As anatomists dissected, undertakers preserved, jewelers encased, and artists figured the corpse, so too the novelist portrayed bodily artifacts. Why are these morbid forms of materiality entombed in the novel? Jolene Zigarovich addresses this complex question by claiming that the body itself--its parts, or its preserved representation--functioned as secular memento, suggesting that preserved remains became symbols of individuality and subjectivity. To support the conception that in this period notions of self and knowing center upon theories of the tactile and material, the chapters are organized around sensory conceptions and bodily materials such as touch, preserved flesh, bowel, heart, wax, hair, and bone. Including numerous visual examples, the book also argues that the relic represents the slippage between corpse and treasure, sentimentality and materialism, and corporeal fetish and aesthetic accessory.Zigarovich's analysis compels us to reassess the eighteenth-century response to and representation of the dead and dead-like body, and its material purpose and use in fiction. In a broader framework, Death and the Body in the Eighteenth-Century Novel also narrates a history of the novel that speaks to the cultural formation of modern individualism.
Frontmatter -- Contents -- Illustrations -- Introduction -- Chapter 1 Secularism, Materialism, and Death in the Eighteenth Century -- Chapter 2 Preserving Clarissa Eighteenth-Century Embalming Practices -- Chapter 3 Waxen Encounters Flesh, Anatomy, and Autonomy -- Chapter 4 Circulating Bodies Secular Mementos, Jewelry, and Hairwork -- Chapter 5 Osseous Matter Bones, Relics, and Mourning Miniatures -- Afterword -- Notes -- Bibliography -- Index -- Acknowledgments
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 15, 2022).
In English.
JSTOR
Keywords: English fiction -- 18th century -- History and criticism; Death in literature; Dead in literature; Mourning customs -- Great Britain -- History -- 18th century; Human body in literature; Mourning customs in literature; Relics in literature; Roman anglais -- 18e siècle -- Histoire et critique; Mort dans la littérature.; Morts dans la littérature.; Deuil -- Coutumes -- Grande-Bretagne -- Histoire -- 18e siècle.; Corps humain dans la littérature.; Deuil -- Coutumes, dans la littérature.; Reliques dans la littérature.; LITERARY CRITICISM / Modern / 18th Century .; Dead in literature; Death in literature; English fiction; Human body in literature; Mourning customs; Mourning customs in literature; Relics in literature; Great Britain; 1700-1799; British novel; Clarissa; Enlightenment; Samuel Richardson; anatomy; bodies; corpse; dead body; death; deathbed; dissection; eighteenth century; fiction; material culture; mourning; necropolitics; relics; scene; science; secularism; senses; sentimentality; Electronic books; Criticism, interpretation, etc; History; Literary criticism; Literary criticism; Critiques littéraires.